Optimizing Real-Time Advanced Ultrasound Supervision in a University Setting - Nina Hanger; Lydia Johnsen; Ruth Stoklund; Ragna Stalsberg (Radiography Open, 2024)
Introduction: Ultrasound-based diagnosis requires great expertise for reliability and accuracy, thus practical training is vital. Digital training can offer students the possibility of practical training in their local setups. However, there are critical issues that remote educators must address, particularly in advanced ultrasound training. The present study was therefore aiming at developing a suitable technical setup for supervision and education in tele-ultrasound that can be applied to a variety of advanced diagnostic and therapeutic areas.